Utilization of Host-Derived Glycans by Intestinal Lactobacillus and Bifidobacterium Species - Zúñiga, Manuel; Monedero, Vicente; Yebra, María J. (Frontiers in Microbiology, 2018)
Members of the genus Lactobacillus are commonly found at the gastrointestinal tract and other mucosal surfaces of humans. This genus includes various species with a great number of potentially probiotic bacteria. Other often-used probiotic species belong to Bifidobacterium, a genus almost exclusively associated with the gut. As probiotics must survive and be metabolically active at their target sites, namely host mucosal surfaces, consumption of host-produced glycans is a key factor for their survival and activity. The ability to metabolize glycans such as human milk oligosaccharides (HMOs), glycosaminoglycans and the glycan moieties of glycoproteins and glycolipids found at the mucosal surfaces grants a competitive advantage to lactobacilli and bifidobacteria. The analyses of the great number of sequenced genomes from these bacteria have revealed that many of them encode a wide assortment of genes involved in the metabolism and transport of carbohydrates, including several glycoside hydrolases required for metabolizing the carbohydrate moieties of mucins and HMOs. Here, the current knowledge on the genetic mechanisms, known catabolic pathways and biochemical properties of enzymes involved in the utilization of host-produced glycans by lactobacilli and bifidobacteria will be summarized.